A combined power and steam system integrated with solar photovoltaic/thermal collector: Thermodynamic characteristics and cost-benefit analyses. (November 2022) - Wang, Jiangjiang; Chen, Haiyue; Deng, Hongda; Dong, Fuxiang
Abstract: This paper proposes a combined power and steam system integrated with solar photovoltaic/thermal collectors. The system uses solar energy and natural gas to generate electricity and recovers waste heat from the internal combustion engine and solar collectors to produce steam through the absorption heat transformer. In this paper, the thermodynamic model of each subsystem is established, and the thermodynamic performances of the system are analyzed. The results show that the energy efficiency and exergy efficiency of the system are 56.8% and 33.4% under the design conditions, respectively. The exergy efficiency of the absorption heat transformer was 80.8%, and the exergy efficiency of the collectors was only 15.2%. Under variable working conditions, the coverage rate of photovoltaic modules and the load rate of the internal combustion engine have a positive effect on the system performance. In contrast, solar radiation intensity plays a negative role in the power generation efficiency of photovoltaic modules. Compared with the conventional electric boiler system for producing steam, the cost-saving rate of per ton vapor is 9.4%. The application analysis of the system shows that the solar resource in different regions and the ICE operation time throughout the year have a significant impact on the system output.